(untitled) (Asian Journal of Medical and Biological Research, 2022)
Soybean mosaic virus (SMV) is the major constraints for soybean cultivation in many parts of the country. Experiments were carried out to study the seed transmission of SMV and to identify the resistant sources through screening of 30 promising soybean genotypes obtained from different sources under natural infections conditions in between 2000 and 2001. Indirect-ELISA was performed against TRSV, TMV, CPMV, CMV, BBSV, BBTMV and SMV in leaf materials, both from healthy and diseased plant materials and the results showed that the seeds and the plants in the field were free from those 6 viruses. The highest seed transmission was found in Gaurab (15.07%) followed by G-2120 and the lowest (1.5%) seed transmission was found in TG-893 followed by BS-32, CM and AGS-129. Seed mottling was found related to seed transmission. No disease incidence was found in AGS-129 but there were seed mottling (1.25%). On the other hand, genotype AGS- 160 was free from mottled seeds but produced infected seedlings. Mosaic symptom became apparent 15 days after sowing (DAS), highest at 60 DAS and disappear after 90 DAS. Seeds from seed lot containing up to 20% mottled symptom could not hamper production. Screening of 30 soybean genotypes based on the natural infections revealed that AGS-129 was identified as resistant and grading 1, 10 were identified as moderately resistant (MR) considered as grading 3 and the remaining genotypes were susceptible (S) and moderately susceptible (MS) considered as grading 7 and 5, respectively. The 10 genotypes viz. CM, BS-32, ACAGS-154, G-2261, AGS-129, Durga, Williams, AGS-160, EC-1178 and PR-164 could be used for further study to locate resistant genes against soybean mosaic virus and varietal improvement in breeding purpose. Asian J. Med. Biol. Res. 2022, 8 (1), 47-62